2015
DOI: 10.1155/2015/728925
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in Inflammatory Bowel Disease Outpatients: Prevalence, Risk Factors, and Etiology

Abstract: Anemia is common in inflammatory bowel disease (IBD). However, epidemiological studies of nonwestern IBD populations are limited and may be confounded by demographic, socioeconomic, and disease-related influences. This study evaluated the prevalence, risk factors, and etiology of anemia in Brazilian outpatients with IBD. Methods. In this cross-sectional study, 100 Crohn's disease (CD) patients and 100 ulcerative colitis (UC) subjects were assessed. Anemia workup included complete blood count, ferritin, transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
3
34
0
2
Order By: Relevance
“…This prevalence is slightly higher than that published recently in a meta-analysis by Filmann et al: 24% of 2,192 European patients with IBD had anemia [7]. Other studies show that up to 68% of inpatients with IBD had anemia [8,9]. The differences between the prevalence of anemia in IBD depend strongly on the studied population; for example, in the study of Bager et al, the study population consisted only of outpatients with IBD and anemia prevalence was found to be 19% [10].…”
Section: Discussionmentioning
confidence: 54%
“…This prevalence is slightly higher than that published recently in a meta-analysis by Filmann et al: 24% of 2,192 European patients with IBD had anemia [7]. Other studies show that up to 68% of inpatients with IBD had anemia [8,9]. The differences between the prevalence of anemia in IBD depend strongly on the studied population; for example, in the study of Bager et al, the study population consisted only of outpatients with IBD and anemia prevalence was found to be 19% [10].…”
Section: Discussionmentioning
confidence: 54%
“…Anemia has been associated with an individual prognostic factor for mortality in other studies . In our study, we report the association between anemia, ID, IDA, and IDWA and in‐hospital mortality.…”
Section: Discussionmentioning
confidence: 59%
“… 4 Patients with CD are more likely to be anaemic than those with UC. 18 20–23 There are several potential causes of anaemia in IBD including iron deficiency, anaemia of chronic disease, vitamin B 12 deficiency, folate deficiency and drug-induced anaemia. 7 8 16 18–21 Multiple types of anaemia may be present concurrently.…”
Section: Introductionmentioning
confidence: 99%